Racism in Maternity Care is a Public Health Crisis in the United States. Issue 5 (September 2021) - Simpson, Kathleen Rice
Abstract : There is ample evidence that racism is a public health crisis in the United States. In maternity care, racism as a factor in maternal morbidity and mortality is highlighted in the significant disparities in outcomes when comparing women of various racial and ethnic backgrounds. The National Center for Health Statistics reported over 750 women in the United States died of maternal causes in 2019. Deaths are higher among women in minorized groups, identified by the National Vital Statistics System as non-Hispanic Black women. Recent evidence about maternal mortality and reports suggesting ways to improve maternity care in the United States are reviewed.